Strengthening Indonesia’s Financial Consumer Protection Framework: A Comparative Analysis of the U.S. Consumer Financial Protection Bureau - Tri Herdianto; Dewi Sulistianingsih; Pujiono (Universitas Muhammadiyah Purwokerto, 2026)
This research examines the legal standing and statutory authority of the Financial Services Authority (Otoritas Jasa Keuangan, OJK) to commence civil proceedings on behalf of consumers in Indonesia’s financial services sector, a mandate that has gained increasing relevance amid the expansion of complex financial products and digital delivery channels. Grounded in Law No. 21 of 2011 and its implementing regulations, OJK’s litigation power is conceptualised as a regulatory enforcement mechanism intended to address structural consumer disadvantages, strengthen institutional accountability, and promote compliance with market-conduct norms. The analysis situates this authority within broader doctrinal frameworks, including public interest litigation, administrative law principles, and regulatory enforcement theory. To provide comparative context, the article briefly contrasts OJK’s mandate with the enforcement powers of the United States Consumer Financial Protection Bureau (CFPB), a leading model in consumer-focused financial regulation. Using a normative juridical methodology, the article evaluates the practical effectiveness of OJK-initiated civil actions and compares them with alternative redress mechanisms, such as class actions. The findings indicate that despite a clear statutory foundation, OJK’s use of civil litigation remains limited by procedural uncertainties and institutional preferences for non-judicial approaches. Nevertheless, OJK-filed lawsuits hold significant potential to enhance remedial access, improve evidentiary processes, and create stronger deterrence against market misconduct. The study concludes that clearer procedural guidelines and strengthened institutional capacity are essential to optimise OJK’s role in consumer protection.